2005
DOI: 10.1038/sj.npp.1300795
|View full text |Cite
|
Sign up to set email alerts
|

A Reduced Rate of In Vivo Dopamine Transporter Binding is Associated with Lower Relative Reinforcing Efficacy of Stimulants

Abstract: A slow onset of action has been hypothesized to weaken the reinforcing effects of drugs. The present study evaluated this hypothesis with slow-onset cocaine analogs, WIN 35428, RTI 31, and RTI 51. When cocaine or a cocaine analog was made available to rhesus monkeys (n ¼ 4 or 5) for self-administration under a progressive-ratio (PR) schedule with a 1-h time-out between injections, all the drugs functioned as positive reinforcers. The maximum number of injections was in the order of cocaine4WIN 354284RTI 314RTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Lile et al (2000) suggested that the impact of uptake and distribution on binding association kinetics is a critical factor in reinforcing effectiveness of DAT inhibitors. In their study, 2␤-propanoyl-3␤-(4-tolyl)-tropane, a DAT inhibitor with reduced reinforcing effectiveness in primates, had a lower apparent DAT association rate compared with cocaine in rats, presumably because of slower uptake and distribution (see also Wee et al, 2006;Kimmel et al, 2008). However, as also noted (Woolverton et al, 2002;, actions at other sites may obscure relationships between reinforcing effectiveness and rate of DAT occupancy.…”
Section: Discussionmentioning
confidence: 98%
“…Lile et al (2000) suggested that the impact of uptake and distribution on binding association kinetics is a critical factor in reinforcing effectiveness of DAT inhibitors. In their study, 2␤-propanoyl-3␤-(4-tolyl)-tropane, a DAT inhibitor with reduced reinforcing effectiveness in primates, had a lower apparent DAT association rate compared with cocaine in rats, presumably because of slower uptake and distribution (see also Wee et al, 2006;Kimmel et al, 2008). However, as also noted (Woolverton et al, 2002;, actions at other sites may obscure relationships between reinforcing effectiveness and rate of DAT occupancy.…”
Section: Discussionmentioning
confidence: 98%
“…One factor thought to impact the rewarding efficacy of a given psychostimulant is the rate at which the compound enters the brain and interacts with the DAT; compounds with a rapid onset of action tend to exhibit greater addictive potential than do those with a slower onset rate (Wee et al, 2006). Even cocaine was found to have lower reinforcing efficacy in a primate progressive-ratio selfadministration paradigm when injected over a period of 10 minutes, as opposed to a period of 10 seconds (Woolverton and Wang, 2004).…”
Section: Atypical Uptake Inhibitors: Conformationspecific Binding Mecmentioning
confidence: 99%
“…Monkey 96R0679 had a history of self-administration of the phenyltropane RTI-31 under a fixed-ratio 1 (FR1) schedule of reinforcement (Wee et al 2006). Monkeys RiK2, R0697, M1338, and R0463 had self-administered a variety of compounds under PR schedules similar to the one used here (Woolverton et al 2008).…”
Section: Animals and Apparatusmentioning
confidence: 99%